P. mirabilis-derived pore-forming haemolysin, HpmA drives intestinal alpha-synuclein aggregation in a mouse model of neurodegenerationResearch in context - Eugene Huh; Jin Gyu Choi; Yujin Choi; In Gyoung Ju; Bora Kim; Yoon-Jung Shin; Jong Min An; Myoung Gyu Park; Sung Vin Yim; Su Jin Chung; Sang-Uk Seo; Dokyoung Kim; et al. (EBioMedicine, 2023)
Summary: Background: Recent studies suggesting the importance of the gut-microbiome in intestinal aggregated alpha synuclein (α-syn) have led to the exploration of the possible role of the gut-brain axis in central nervous system degeneration. Proteus mirabilis (P. mirabilis), a gram-negative facultative anaerobic bacterium, has been linked to brain neurodegeneration in animal studies. We hypothesised that P. mirabilis-derived virulence factors aggregate intestinal α-synuclein and could prompt the pathogenesis of dopaminergic neurodegeneration in the brain. Methods: We used vagotomised- and antibiotic-treated male murine models to determine the pathogenesis of P. mirabilis during brain neurodegeneration. The neurodegenerative factor that is driven by P. mirabilis was determined using genetically mutated P. mirabilis. The pathological functions and interactions of the virulence factors were determined in vitro. Findings: The results showed that P. mirabilis-induced motor dysfunction and neurodegeneration are regulated by intestinal α-syn aggregation in vagotomised- or antibiotic-treated murine models. We deduced that the specific virulence factor, haemolysin A (HpmA), plays a role in the pathogenesis of P. mirabilis. HpmA is involved in α-synuclein oligomerisation and membrane pore formation, resulting in the activation of mTOR-mediated autophagy signalling in intestinal neuroendocrine cells. Interpretation: Taken together, the results of the present study suggest that HpmA can interact with α-syn and act as a possible indicator of brain neurodegenerative diseases that are induced by P. mirabilis. Funding: This study was supported by a grant from the National Research Foundation of Korea.